Pediatric Idiopathic Intracranial Hypertension: A Case Report. - Nandwani, Divya; Vricella, Marilyn; Richter, Scott (Optometry & Visual Performance, 2015)
Background: Idiopathic intracranial hypertension (IIH) presents differently in prepubertal children as compared to postpubertal children and adults. In adults, IIH is most common in obese women of child-bearing age. However, when occurring in prepubertal children, IIH has been shown to have no predilection for gender and does not correlate with obesity. This case report exemplifies the rare occurrence of IIH in a pediatric patient. Case Report: A five-year-old Hispanic female patient was seen at the University Eye Center for a longstanding hypotropia secondary to a likely congenital fourth nerve palsy with an exotropia component. After a strabismus surgery and a series of follow-up visits, bilateral swollen optic nerves were observed, and a prompt referral to the emergency room was made. Consequently, she was diagnosed with IIH. A treatment regimen of acetazolamide was initiated with subsequent improvement of the clinical presentation of increased intracranial pressure, confirmed by the reduction of swelling of her optic nerves. Conclusions: Bilateral swelling of the optic nerves can be an emergency, especially in children. It is important urgently to rule out causes for increased intracranial pressure. If treatment is significantly delayed, or if no treatment is given to a patient with this condition, loss of visual function may occur. In addition to reporting a rare circumstance of pediatric idiopathic intracranial hypertension, this case report serves to remind eye care practitioners of the importance of monitoring the ocular health of patients closely, even in young, healthy children.